1974
DOI: 10.2307/1218776
|View full text |Cite
|
Sign up to set email alerts
|

Betalains and P‐type Sieve‐tube Plastids in Petiveria and Agdestis (Phytolaccaceae)

Abstract: SummaryThe discovery of betalains and P‐type sieve‐tube plastids in Petiveria and Agdestis (Phytolaccaceae) supports the assignment of these genera to the Centrospermae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1980
1980
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Chemical and ultrastructural data have shown that Agdestis is properly placed in the Caryophyllales (Behnke et al, 1974). In the neighbor-joining tree (not shown here), Agdestis showed close relationships with Sarcobatus (Sarcobataceae).…”
Section: Discussionmentioning
confidence: 67%
“…Chemical and ultrastructural data have shown that Agdestis is properly placed in the Caryophyllales (Behnke et al, 1974). In the neighbor-joining tree (not shown here), Agdestis showed close relationships with Sarcobatus (Sarcobataceae).…”
Section: Discussionmentioning
confidence: 67%
“…Some families in the Caryophyllales have a unique kind of sieve-element plastid in which there are ring-shaped bundles of filaments that contain protein; these plastids are called P-type plastids (Behnke, 1972). There is another basic kind of sieve-element plastid in which starch is accumulated, and it is called an S-type plastid (Behnke, 1972(Behnke, , 1976(Behnke, , 1991Behnke et al, 1974). The non-core families in the Caryophyllales have S-type sieve-element plastids, and the core families have P-type, except the Asteropediaceae, Physenaceae and Simmondsiaceae, which have S-type (Table 1).…”
Section: Caryophyllalesmentioning
confidence: 99%